Amizade e sua relação com o turismo: perspectivas psicológicas - Nunes, Tatiana Amaral (2017)
The present research had as objective to describe the role of the friends in the accomplishment of tourist activities and as specific contexts of tourism affect the relationships of friendships. For that, three independent studies were carried out, with different participants and different tourist contexts: (1) Friendship and its relations with Religious Cultural Tourism: perspectives of the third age; (2) Friendship and its relationship with Sun and Beach Tourism according to a vision of women and; (3) Friendship and its relationship with Fishing Tourism according to a vision of men. The method used by each study for qualitative field research with descriptive characteristics, having as basic plan the study of single and multiple cases. The results and analyzes obtained with the first study indicate that regardless of religion, a friendship and religious cultural tourism are factors that are associated in the third age. However, the data collected by the study showed that the friendship of women and their relationship with sun and beach tourism are factors that are little associated, since this type of leisure is preferentially done with the family. Finally, considerably for the findings of the first study, a third survey showed that friendship between men is central to experiences in the context of fishing. The present proposal concluded that there is a correspondence between a friendship and tourism, a more intense association in the contexts of religious tourism in the third age and the tourism of fishing between the men, emphasizing a social interaction and happiness as the main benefits and function of the friendship, considering Leisure as one of its contexts of development and strengthening of ties. Because tourism is an activity with different modalities and possibilities of experimentation, it is suggested that new tourist contexts are studied in order to expand as analyzes on the effect of friendship as well as other interpersonal relationships related to this type of leisure.